2014
DOI: 10.1111/epi.12762
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation for drug‐resistant epilepsy: A European long‐term study up to 24 months in 347 children

Abstract: SUMMARYObjective: To gain insight into the long-term impact of vagus nerve stimulation (with VNS Therapy) in children with drug-resistant epilepsy, we conducted the largest retrospective multicenter study to date over an extended follow-up period of up to 24 months. Methods: The primary objective was to assess change in seizure frequency of the predominant seizure type (defined as the most disabling seizure) following VNS device implantation. Treating physicians collected data from patient records from baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
181
4
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(219 citation statements)
references
References 28 publications
17
181
4
11
Order By: Relevance
“…Similarly, VNS also played a relevant role in the management of refractory epilepsy in children, as observed in one of the major retrospective multicenter studies, which analyzed 347 children and found that 32.5% were responsive patients after six months, 37.6% after 12 months and 43.8% after 24 months 8 . When comparing patients younger and older than 12 years, no significant difference in efficacy or complication rate was demonstrated after five years of follow-up in 141 patients 39 , although some reported increased infection rates in children 40 .…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, VNS also played a relevant role in the management of refractory epilepsy in children, as observed in one of the major retrospective multicenter studies, which analyzed 347 children and found that 32.5% were responsive patients after six months, 37.6% after 12 months and 43.8% after 24 months 8 . When comparing patients younger and older than 12 years, no significant difference in efficacy or complication rate was demonstrated after five years of follow-up in 141 patients 39 , although some reported increased infection rates in children 40 .…”
mentioning
confidence: 85%
“…These were followed by double-blind, randomized studies, which were extremely relevant for the establishment of vagus nerve stimulation as an option for refractory epilepsy treatment and were also considered evidence for therapy approval by regulatory agencies in Europe and in the United States. Vagus nerve stimulation therapy was approved by the European community in 1994 and by the American community in 1997 and, nowadays, more than 70,000 patients have had implants for the treatment of epilepsy or depression 8 .…”
mentioning
confidence: 99%
“…The cuff electrode is routinely used in the clinical setting for vagus nerve stimulation (VNS), which has been shown to be effective in the management of epilepsy [31,104], resistant depression [127], blood pressure control [110], as well as prevention of heart failure in patients with reduced ejection fractions [32,43,113]. Additionally, the Inspire® hypoglossal nerve stimulator, a Food and Drug Administration (FDA)- Fig.…”
Section: Cuff Electrodesmentioning
confidence: 99%
“…Management of patients who have recurrent seizures and did not respond to medication or surgery is challenging. A number of double-blind randomized controlled trials have confirmed the therapeutic effects of Vagus Nerve Stimulation [VNS] for epilepsy [66][67][68][69]. A recent European long-term study [n=347] showed a 50% reduction in seizure frequency for up to 43.8% of patients [66].…”
Section: Neuromodulation For Epilepsymentioning
confidence: 99%
“…A number of double-blind randomized controlled trials have confirmed the therapeutic effects of Vagus Nerve Stimulation [VNS] for epilepsy [66][67][68][69]. A recent European long-term study [n=347] showed a 50% reduction in seizure frequency for up to 43.8% of patients [66]. Greater treatment effect has been observed with higher VNS settings [66].…”
Section: Neuromodulation For Epilepsymentioning
confidence: 99%